Investigating the effect of Azospirillum brasilense and Rhizobium pisi on agronomic traits of wheat (Triticum aestivum L.). Issue 11 (19th September 2019) - Zaheer, Muhammad Saqlain; Raza, Muhammad Aown Sammar; Saleem, Muhammad Farrukh; Khan, Imran Haider; Ahmad, Salman; Iqbal, Rashid; Manevski, Kiril
ABSTRACT: Plant growth-promoting rhizobacteria (PGPR) play an important role in improving crop growth but have not been studied sufficiently. A wire house experiment was conducted in Pakistan to determine the combined effect of inoculating wheat seeds with PGPR on the subsequent growth and yield of the wheat. The experiment included four treatments: T0 – no-inoculation (control), T1 – Azospirillum brasilense inoculation, T2 – Rhizobium pisi inoculation and T3 – co-inoculation with A. brasilense and R. pisi . Development and growth attributes, as well as final yield of wheat, were studied. Co-inoculation of seeds with both strains increased significantly wheat grain yield, the number of grains per plant and 1000-grain weight by 36%, 11% and 17%, respectively, compared to non-inoculated control. While crop growth rate increased for, respectively, 5.5% and 33% at tillering and flag leaf stages, corresponding values for T3 were about 9% and 14% higher than values for sole inoculations in T1 and T2 . Co-inoculation also significantly increased leaf epicuticular wax and relative water content as compared to the control treatment. Thus, inoculation of wheat seeds with A. brasilense and R. pisi and their combination is a promising method to improve growth, yield and quality of wheat.